Role of Development of the Agro-Industrial Complex to Create Areas of Agritourism - RAKHIMBERDINOVA, Madina; NUREKENOVA, Elvira; ORDABAYEVA, Mainur; KONYRBEKOV, Medet; SAIFULLINA, Yulia; KUTTYBAEVA, Nurgul (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022DO - 10.14505/jemt.v13.8(64).23, 2022)
Agritourism is rapidly developing in many countries, but despite this, little is known about the specific implementation, the actual scope and effectiveness of public and private measures to support the development of agriculture and agritourism, especially in recent times. Therefore, the purpose of this study is to analyze the development of agro-industrial complex for the creation of agrotourism zones on the materials of the Republic of Kazakhstan. The integration of agrotourism is a breakthrough for the prosperity of rural industry and the revitalization of rural areas. In addition, agricultural eco-efficiency and the integration of agro-tourism are closely related, so studying the relationship between them is of great importance for realizing high-quality agro-ecological development.